Obstacle Avoidance Functions on Robot Mirosot in the Departement of Informatics of UPN “Veteran” - Wilis Kaswidjanti; Hidayatulah Himawan; Awang Hendrianto Pratomo; Hafidz Fajar Abdur Rahman (IAES Indonesia Section, 2015)
The robot is a machine that can perform physicalactivity repeatedly, either with human control or worksautomatically with the use of artificial intelligence. In the process,the robot can perform various kinds of sports, one of which is abranch of football. Robot football match organized by theFederation of International Robot-Soccer Association (FIRA)consists of several categories, one of which Micro Robot SoccerTournament (MiroSot). MiroSot is five to five games consisting of arobot measuring 7.5 cm x 7.5 cm x 7.5 cm were able to move andadapt to the environment without human intervention. CurrentlyInformatics UPN